Service & non-profit marketing - Stanković Čedomir (Marketing (Beograd. 1991), 2002)
Services are dominantly untouchable products which cannot be physically owned. Services promotion is difficult for its untouchables. Personal sale is very powerful in service companies because customers must interact with employees. Price is very important for service's companies. It has psychological role, economic role and it creates attitude for goal achievement. Marketing goal for nonprofit organizations is to get an answer from target market Development of marketing strategies of nonprofit organizations consists of defining and analyzing target market and creating and maintaining marketing mix. In nonprofit organizations product is usually an idea or a service. Promotion in nonprofit organizations is very important. Personal sale, promotional sale, advertising and publicity are used for communicating an idea and informing people about services.